Teachers Acceptance of the Use of Smartboard in Riyadh Region, Saudi Arabia - Hashim, Sulaiman; Nordin, Mohamad Sahari (2020)
This study aimed to validate an extended Unified Theory of Acceptance and Use of Technology (UTAUT) based on the data derived from mathematics teachers of Riyadh Region, Saudi Arabia. Taking into account perceived enjoyment, anxiety, and self-efficacy in using smartboard, the study extended the original UTAUT model. It assessed the effects of these three main factors on the teachers' behavioural intention to use smartboard. The study evaluated computer training-invariant of the causal structure of the hypothesized model. The data were collected from a self-reported questionnaire administered to 150 female mathematics teachers in the Saudi intermediate public schools in Riyadh. The results of structural equation modeling supported the adequacy of the hypothesized interrelationships. Moreover, computer training groups appeared to moderate the structural relationships among the constructs of the extended model.